Rice yield formation under high day and night temperatures—A prerequisite to ensure future food security - Xu, Jiemeng; Henry, Amelia; Sreenivasulu, Nese (Wiley, 2020)
Increasing temperatures resulting from climate change dramatically impact rice crop production in Asia. Depending on the specific stage of rice development, heat stress reduces tiller/panicle number, decreases grain number per plant and lower grain weight, thus negatively impacting yield formation. Hence improving rice crop tolerance to heat stress in terms of sustaining yield stability under high day temperature (HDT), high night temperature (HNT), or combined high day and night temperature (HDNT) will bolster future food security. In this review article, we highlight the phenological alterations caused by heat and the underlying molecular‐physiological and genetic mechanisms operating under different types of heat conditions (HDT, HNT, and HDNT) to understand heat tolerance. Based on our synthesis of HDT, HNT, and HDNT effects on rice yield components, we outline future breeding strategies to contribute to sustained food security under climate change.